2006
DOI: 10.1105/tpc.106.046151
|View full text |Cite
|
Sign up to set email alerts
|

MAIGO2 Is Involved in Exit of Seed Storage Proteins from the Endoplasmic Reticulum in Arabidopsis thaliana

Abstract: Seed storage proteins are synthesized on the endoplasmic reticulum (ER) as precursors and then transported to protein storage vacuoles, where they are processed into mature forms. Here, we isolated an Arabidopsis thaliana mutant, maigo2 (mag2), that accumulated the precursors of two major storage proteins, 2S albumin and 12S globulin, in dry seeds. mag2 seed cells contained many novel structures, with an electron-dense core that was composed of the precursor forms of 2S albumin. 12S globulins were segregated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 49 publications
1
108
0
2
Order By: Relevance
“…An Arabidopsis thaliana mutant, maigo2 (mag2), accumulated the precursors of two major storage proteins, 2S albumin and 12S globulin, in dry seeds. MAG2 functions in the transport of storage protein precursors between the ER and Golgi apparatus in plants (Li et al 2006). A type I membrane protein, AtVSR1/AtELP, of Arabidopsis functions as a sorting receptor for storage proteins.…”
Section: Discussionmentioning
confidence: 99%
“…An Arabidopsis thaliana mutant, maigo2 (mag2), accumulated the precursors of two major storage proteins, 2S albumin and 12S globulin, in dry seeds. MAG2 functions in the transport of storage protein precursors between the ER and Golgi apparatus in plants (Li et al 2006). A type I membrane protein, AtVSR1/AtELP, of Arabidopsis functions as a sorting receptor for storage proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Plants can transport proteins from the ER into vacuoles both through Golgi-dependent and Golgi-independent pathways Li et al, 2006;Shimada et al, 2006;Fuji et al, 2007). Indeed, Teh and Moore (2007) reported that gnl1 mutants, which are allelic to ermo1 mutants, accumulate secretory GFP in the ER.…”
Section: Gnl1/ermo1 and Sec24a/ermo2 May Have Roles In Maintaining Ermentioning
confidence: 99%
“…The development of the vamp727 syp22 double mutant was arrested at a late step of embryogenesis, suggesting an essential function of the VAMP727 complex in normal seed maturation. The small PSVs or faulty processing of storage proteins are probably not alone responsible for the lethality because many mutants with similar phenotypes have been reported to be viable (Shimada et al, 2003a(Shimada et al, , 2003bLi et al, 2006;Shimada et al, 2006;Fuji et al, 2007;Tamura et al, 2007). There should be additional defects in the vamp727 syp22 mutant that severely affect the viability of seeds.…”
Section: Online)mentioning
confidence: 99%